A22 Medium-sized spiny neurons diversity in Huntington's disease pathology. (12th September 2022) - Bergonzoni, Guendalina; Ferrarini, Denise; Savino, Aurora; Gillis, Tammy; Casiraghi, Nicola Andrea; Geurs, Sarah; Tebaldi, Michele; Poli, Valeria; Romanel, Alessandro; Voet, Thierry; Wheeler, Vanessa C; Dassi, Erik; et al.
Abstract : The first degenerating brain region in Huntington's disease (HD) is the striatum, with dopamine receptor 2 (D2R) medium-sized spiny neurons (MSNs) displaying relatively greater vulnerability to degeneration compared to dopamine receptor 1 (D1R) MSNs. To dissect this differential sensitivity, we integrated morphological, transcriptional, genomic, and somatic instability analyses to explore potential dissimilarities. Two Htt CAG knock-in mouse models harboring 18 ( Htt Q20 : 'control') or 190 ( Htt Q175 : 'HD') consecutive CAG repeats, expressing tdTomato and EGFP fluorescent proteins under the control of Drd1 and Drd2 promoters, respectively, were used. By immunofluorescence experiments, we characterized the distribution of MSNs and their tendency to accumulate nuclear mutant huntingtin, across different striatal regions and throughout various disease stages. We then collected 8 week-old mice D1R- and D2R-MSN pools and single cells, on which we performed genomic and transcriptomic sequencing, and somatic instability analyses. From morphologic analyses, D1R-MSNs are more abundant than D2R-MSNs in the control condition and continue to outnumber D2R-MSNs in the HD model. D1R-MSNs accumulate more diffuse nuclear staining for mutant huntingtin than D2R-MSNs which, instead, show higher numbers of huntingtin aggregates. D1R-MSNs also activate greater transcriptomic changes, increasing the expression levels of genes implicated in OXPHOS and transcription pathways, while D2R-MSNs seem less responsive. On a genomic DNA level, we did not detect any large copy number variation in either of the two MSNs, while a modestly stronger somatic CAG repeat expansion was identified in D2R-MSNs. We hypothesize that D1R-MSNs activate protective transcriptional changes, while D2R-MSNs may show higher susceptibility to repeat expansion.